2018
DOI: 10.1016/j.jamcollsurg.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Image-Based Mobile Health Protocol for Postoperative Wound Monitoring

Abstract: Patients and their caregivers are willing to participate in a mobile health program aimed at remote monitoring of postoperative recovery, and they are able to complete it with a high level of fidelity and satisfaction. Preliminary results indicate the ability to detect and intervene on wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
140
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 36 publications
1
140
0
4
Order By: Relevance
“…Skill acquisition of wound care, on the other hand, occurred more quickly with both groups, but the magnitude was greater for mHealth users. Gunter et al () reported on the use of an image‐based mHealth protocol for post‐operative wound monitoring; however, its purpose was the detection of wound complications and participants’ satisfaction, making comparisons with our study difficult.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Skill acquisition of wound care, on the other hand, occurred more quickly with both groups, but the magnitude was greater for mHealth users. Gunter et al () reported on the use of an image‐based mHealth protocol for post‐operative wound monitoring; however, its purpose was the detection of wound complications and participants’ satisfaction, making comparisons with our study difficult.…”
Section: Discussionmentioning
confidence: 86%
“…The mHealth app is currently available only for the Android operating system, albeit the worldwide market shares of Android (76.08%) is greater than iOS (22.01%) (Statcounter, ). Future studies should consider patient satisfaction (Gunter et al, ), effects on quality of life, clinical outcomes, and usage rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations